ANALYSIS OF MARKETING STRATEGIES IN INCREASING THE NUMBER OF CUSTOMERS IN PERUMDA BPR BANK GRESIK - Isnainiah Rachmawati; Wenti Krisnawati (Faculty of Economic and Business, University of Pasundan, 2022)
The objective of this research is to determine the application of marketing strategies in increasing the number of customers at PERUMDA BPR Bank Gresik. A qualitative descriptive method was implemented in this research, which is intended to collect facts and elaborate in a detailed and thorough manner according to the problem to be solved. SWOT analysis (Strengths, Weaknesses, Opportunities, dan Threats) was also employed in this research to find out the strategy conducted by PERUMDA BPR Bank Gresik in increasing the number of customers. The results show that company situation is in Quadrant I (+,+), Progressivity, PERUMDA BPR Bank Gresik carried out economic and trustworthy services to implement the company vision and mission. This position indicates that the company is in a strong position and is already on track. In the future, company still needs to make efforts to maintain this position.